Effects of awake prone position vs. usual care on acute hypoxemic respiratory failure in patients with COVID-19: A systematic review and meta-analysis of randomized controlled trials - Peng, Qing; Yang, Sheng; Zhang, Yu; Zhao, Wenjie; Hu, Man; Meng, Bo; Ni, Huanhuan; Min, Lingfeng; Yu, Jiangquan; Wang, Yongxiang; Zhang, Liang (Frontiers in Medicine, 2023)
Background: Previous studies have shown that awake prone position may be beneficial for the treatment of acute respiratory distress syndrome (ARDS) or acute hypoxic respiratory failure (AHRF) in COVID-19 patients, but the results are not consistent, especially in terms of oxygenation outcomes and intubation rate. This systematic review and meta-analysis assessed the effects of awake prone position on AHRF in COVID-19 patients with all randomized controlled trials (RCTs). Methods: An extensive search of online databases, including MEDLINE, Embase, Web of Science and Cochrane Central Register of Controlled Trials from December 1, 2019 to October 30, 2022, with no language restrictions. This systematic review and meta-analysis are based on the PRISMA statement and has been registered on the International Prospective Register of Systematic Reviews (PROSPERO) with the registered ID: CRD42022367885. We only included RCTs and used Cochrane risk assessment tool for quality assessment. Results: Fourteen RCTs fulfilled the selection criteria and 3290 patients were included. Meta-analysis found that patients in prone position group had more significant improvement in the SpO2/FiO2 ratio (mean difference [MD]: 29.76; 95% confidence interval [CI]: 1.39 to 48.13; P=0.001) compared with usual care. Prone position also reduced the need for intubation (odd ratio [OR]: 0.72; 95% CI: 0.61 to 0.84 ; P＜0.0001; I2=0%). There was no significant difference in mortality, hospital length of stay, incidence of intensive care unit (ICU) admission and adverse events between the two groups. Conclusions: Awake prone position was a promising intervention method, which is beneficial to improve the oxygenation of patients with ARDS or AHRF caused by COVID-19 and can reduce the need for intubation. However, prone position had no significant difference in mortality, hospital length of stay, incidence of ICU admission and adverse events.